Best available technologies in a modern economy: the basis for import substitution and a tool for transition to a circular economy - F. F. Galimulina; M. V. Shinkevich; I. A. Zaraychenko (Вестник университета)
The best available techniques (BAT) today serve as a tool to overcome the turbulence of economic processes. The purpose of the study is to substantiate the role of the best available techniques for modern Russian industry in the face of new challenges. The author’s position is based on a broad view of BAT that goes beyond environmental aspects. In this regard, a conceptual model of BAT is proposed, based on the idea of harmonizing the development goals of industrial systems against the background of sanctions pressure on the Russian economy and technological backwardness of domestic manufacturing enterprises, and convergence of key trends in industrial development, in particular, sustainable development, the ESG concept, the green economy and the closed-loop economy. A distinctive feature of the author’s approach is the expansion of the boundaries of the potential effect, taking into account its correlation with global trends in industrial development. It is proved that the BAT are able to play the role of a springboard to achieve technological sovereignty of Russia. The formulated scientific provisions can be taken into account within the framework of the development of the BAT methodology.